ENDOBRONCHIAL ULTRASOUND(EBUS) GUIDED TRANSBRONCHIAL NEEDLE ASPIRATION OF MEDIASTINAL AND HILAR LYMPH NODES - FIVE YEARS OF EXPERIENCE AT A CANCER SETTING HOSPITAL IN PAKISTAN - Khalid, Usman; Akram, Muhammad Junaid; Butt, Faheem Mehmood; Ashraf, Mohammad Bilal; Khan, Faheem (Journal of Ayub Medical College Abbottabad, 2020)
Background: Endobronchial Ultrasound (EBUS) guided Transbronchial needle aspiration (TBNA) offers a minimally invasive diagnostic tool for mediastinal lymphadenopathy (ML). This study is done with the objective to determine the diagnostic utility of EBUS TBNA for ML in cancer and non-cancer patients. Methods: This cross-sectional study, in which data was collected retrospectively included TBNA cytopathology and microbiology results of all patients who underwent EBUS at Shaukat Khanum Memorial Cancer Hospital and Research Center, Lahore between July 2013 until July 2018. They were analysed to determine sensitivity and specificity of EBUS. Results: Total 609 patients, comprising 362 (59%) male and 470 (77%) cancer patients were included. Mean age was 52+18 years. TBNA cytology was malignant in 118 (25%) cancer and 20 (14%) non-cancer patients. Percentage malignant ML was highest in small cell lung cancer (93%) among thoracic and renal cell carcinoma (35%) among extra thoracic cancers. Only 27% cancer patients with flourodeoxyglucose-18 avid ML had malignant cytology. Sarcoidosis was diagnosed in 115 (19%) patients (sensitivity 91%, specificity 97%) while tuberculosis in 76 (12%) (sensitivity 87% and specificity 98%). EBUS changed management in 76% cancer patients via multidisciplinary meetings with no reported complications and estimated sensitivity and specificity of 98% and 100% respectively. Conclusion: EBUS is an accurate diagnostic tool for ML and can facilitate multidisciplinary cancer care. Keywords: EBUS; TB; cancer; Sarcoidosis